Поэзия второй половины XX века - Ахметьев И. А. (Пушкинская библиотека, 2002)
Содерж. авт.: А. Николаев, А. Баркова, В. Щировский, А. Кочетков, С. Липкин, А. Гитович, П. Васильев и др. Экземпляры: (20181205) / Инвентарный номер: 1816 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: П 67 / ББК: 84(2Рос=Рус)6-4